Usual interstitial pneumonia progressing to nonspecific interstitial pneumonia-like pattern on high-resolution CT with histologic confirmation - Yazaki, Kai (Radiol Case Rep, 2021)
Idiopathic pulmonary fibrosis (IPF) is a progressive and fatal disease. Although high-resolution computed tomography (HRCT) is important for the diagnosis of IPF, the changes in the HRCT findings in IPF are not fully understood. The patient was a 66-year-old man. His HRCT findings had atypically developed from a probable usual interstitial pneumonia pattern to a nonspecific interstitial pneumonia (NSIP) like pattern over 6 years. On the basis of the histologic examination and multidisciplinary discussion, IPF was diagnosed, and nintedanib, administered. This case can be useful for the differential diagnosis of IPF and NSIP.